Financial sustainability in Malaysian public universities: coping with or embracing change? - Mamat, Suaniza; Nik Ahmad, Nik Nazli; Mohd Said, Julia (Emerald, 2021)
Purpose - This paper explores the institutionalisation of a financial sustainability agenda in Malaysian public universities.